Ytriyum oksit ilavesinin koyun hidroksiapatit-%0.5titanyum oksit ikili sistemine etkisi - PAZARLIOĞLU, SÜLEYMAN SERDAR (My University, 2023)
Bu çalışmada 1200, 1250 ve 1300oC sıcaklıklarda sinterlenen tavuk hidroksiapatit (THA)-%0.5titanyum oksit (TiO2) kompozitine ağırlıkça %0.25 ve %0.5 oranlarında ytriyum oksit (Y2O3) ilavesinin etkisi incelenmiştir. Sinterleme işlemleri sonrası THA’ in çapça kısalma oranının artan sıcaklıkla arttığı ve %17.59±0.52’ ye çıktığı, yoğunluk (2.97±0.03 g/cm3 ) ve sertlik (4.35±0.33 GPa) değerlerinin 1250oC’ de en yüksek değerlerine ulaştığı, ancak; 1300oC’ de sırasıyla 2.96±0.01 g/cm3 ’ e ve 4.32±0.18 GPa’ a gerilediği belirlendi. THA’ e ait basma mukavemeti artan sıcaklıkla 145.41±5.00 MPa’ dan 111.09±9.64 MPa’ a gerilemiştir. THA-%0.5TiO2 kompoziti için en yüksek çapça kısalma oranı (%17.52±0.55), yoğunluk (3.00±0.01 g/cm3 ), sertlik (3.97±0.26 GPa) ve basma dayanımı (170.04±5.65 MPa) 1300oC’ de elde edilmiştir. THA-0.5TiO2-Y2O3 üçlü sisteminde en yüksek çapça kısalma %17.67±0.49, yoğunluk 3.08±0.06 g/cm3 , sertlik 4.48±0.39 GPa ve basma dayanımının 181.03±8.71 MPa ile THA-0.5TiO2-0.5Y2O3’ e ait olduğu belirlendi.

In this study, the effect of adding at amount of 0.25% and 0.5% yttrium oxide (Y2O3) to chicken hydroxyapatite (THA)-0.5% titanium oxide (TiO2) composite sintered at 1200, 1250 and 1300oC temperatures was investigated. After the sintering processes, the diametral shrinkage ratio of THA increased with increasing temperature and reached 17.59±0.52 %, the density (2.97±0.03 g/cm3 ) and hardness (4.35±0.33 GPa) values reached their highest values at 1250oC, hovewer; they decreased to 2.96±0.01 g/cm3 and 4.32±0.18 GPa, respectively, at 1300oC. The compression strength of THA decreased from 145.41±5.00 MPa to 111.09±9.64 MPa with increasing temperature. The highest diametral shrinkage (17.52±0.55%), density (3.00±0.01 g/cm3 ), hardness (3.97±0.26 GPa) and compression strength (170.04±5.65 MPa) were obtained at 1300oC for THA-0.5%TiO2 composite. In the THA-0.5TiO2-Y2O3 ternary system, the highest diametral shrinkage is 17.67±0.49%, the density is 3.08±0.06 g/cm3 , the hardness is 4.48±0.39 GPa and the compression strength is 181.03±8.71 MPa for THA0.5TiO2-0.5Y2O3 composite.
Effect of yttrium oxide addition on sheep hydroxyapatite-0.5%titanium dioxide binary system
Keywords: Tavuk Hidroksiapatit; Titanyum Oksit; Ytriyum Oksit; Sinterleme; Chicken Hydroxyapatite; Titanium Oxide; Yttrium Oxide; Sintering